Serotonergic Dysfunction in Patients with Bipolar Disorder Assessed by the Loudness Dependence of the Auditory Evoked Potential - Lee, Kyung-Sang (Korean Neuropsychiatric Association, 2012)
OBJECTIVE: The loudness dependence of the auditory evoked potential (LDAEP) is suggested to be a marker of serotonin system function. This study explored the LDAEP of multiple mood statuses (depression, mania, and euthymia) and its clinical implication in bipolar disorder patients. METHODS: A total of 89 subjects, comprising 35 patients with bipolar disorder, 32 patients with schizophrenia, and 22 healthy controls were evaluated. The bipolar disorder cases comprised 10 depressed patients, 15 patients with mania, and 10 euthymic patients. The N1/P2 peak-to-peak amplitudes were measured at 5 stimulus intensities, and the LDAEP was calculated as the slope of the linear regression. Both cortical and source LDAEP values were calculated. RESULTS: LDAEP varied according to mood statuses, and was significantly stronger in cases of euthymia, depression, and mania. Cortical LDAEP was significantly stronger in patients with bipolar euthymia compared with schizophrenia, stronger in bipolar depression than in schizophrenia, stronger in healthy controls than in schizophrenia patients, and stronger in healthy controls than in patients with bipolar mania. Source LDAEP was significantly stronger in patients with bipolar euthymia, bipolar depression, and bipolar mania compared with schizophrenia, stronger in bipolar euthymia than in bipolar mania. Psychotic features weakened the source LDAEP relative to nonpsychotic features. The severity of the depressive symptom was negatively correlated with source LDAEP. CONCLUSION: These findings suggest that the serotonin activity of patients with bipolar disorder may vary according to mood status. A longitudinal follow-up study should be pursued using drug-naive subjects.